Outcomes and Complications in Management of Congenital Myopathy Early-Onset Scoliosis. Issue 9 (October 2021) - Magee, Lacey; Bram, Joshua T.; Anari, Jason B.; Ramo, Brandon; Mayer, Oscar H.; Matsumoto, Hiroko; Brooks, Jaysson T.; Andras, Lindsay; Lark, Robert; Fitzgerald, Ryan; Truong, Walter; Li, Ying; et al.
Abstract : Background: Congenital myopathies (CMs) are complex conditions often associated with early-onset scoliosis (EOS). The purpose of this study was to investigate radiographic outcomes in CM patients undergoing EOS instrumentation as well as complications. Secondarily, we sought to compare these patients to a population with higher prevalence, cerebral palsy (CP) EOS patients. Methods: This is a retrospective study of a prospectively collected multicenter registry. The registry was queried for EOS patients with growth-sparing instrumentation (vertical expandable prosthetic titanium ribs, magnetically controlled growing rods, traditional growing rod, or Shilla) and a CM or CP diagnosis with minimum 2 years follow-up. Outcomes included major curve magnitude, T1-S1 height, kyphosis, and complications. Results: Sixteen patients with CM were included. Six (37.5%) children with CM experienced 11 complications by 2 years. Mean major curve magnitude for CM patients was improved postoperatively and maintained at 2 years ( P <0.01), with no significant increase in T1-S1 height or maximum kyphosis( P >0.05). Ninety-seven patients with CP EOS were included as a comparative cohort. Fewer CP patients required baseline respiratory support compared with CM patients (20.0% vs. 92.9%, P <0.01). Fifty-four (55.7%) CP patients experienced a total of 105 complications at 2 years. There was no evidence that the risk of complication or radiographic outcomes differs between cohorts at 2 years, though CP EOS patients experienced significant improvement in all measurements at 2 years. Conclusions: EOS CM children face a high risk of complication after growing instrumentation, with similar curve correction and risk of complication to CP patients. Level of Evidence: Level III.